Identification, population dynamics and prey consumption by spiders on rice fields in the Cauca Valley. - BASTIDAS, HAROLD; PANTOJA, ALBERTO; MURILLO, ALBERTO; ZULUAGA, JOSÉ I.; DUQUE, MIRIAM C. (Revista Colombiana de Entomología, 1994)
Spiders are important pest regulators in tropical agroecosystems. The objectives of this work were: to identify the spider species in rice fields in Cauca Valley in Colombia, their population dynamics, and the consumption capacity of the most abundant species. Eleven families were recovered. The most abundant species recorded were: Tetragnatha sp., T straminea Emerton (Tetragnathidae), Phidippus clarus Key (Salticidae), Synaemops rubropunctatum (Thomisidae), Oxyopes salticus Hentz (Oxyopidae), Argiope argentata (Araneidae) and Pardosa near saxatilis (Hentz) (Lycosidae). Exclusion trials were completed under field conditions with Tagosodes orizicolus (Muir)andTetragnatha sp. The spider density of 4 Tetragnatha sp. / m2 regulates T. orizicolus in a 68.6%. Tetragnatha sp. can consume between 0.9-3.5 Tagosodes/adults/day under confinement; S. rubropunctatum consumed 1.8 Tagosodesl days, the same species can also attack and consume 2.5 first instar Spodoptera frugiperda larvae/day, 1.4-second instar S. frugiperda larvae/day and 0.6 6th instar S. frugiperda larvae/day. Argiope argentata consumed 4.1 adult Tagosodes/day. Phidippus clarus consumed an average of 1.8 Tagosodes nymph/day, and 1.4 III instar and 0.6 IV instar nymphs of Oebalus ornatus /day.